2022
DOI: 10.17398/2340-2784.44.179
|View full text |Cite
|
Sign up to set email alerts
|

Popularizing science – Analyzing the presenter’s multimodal orchestration in a TED Talk

Abstract: In today’s neoliberal economy, digital platforms have led to a proliferation in science popularization where scientists package their messages for the wider public. Our study explores how science ideas are disseminated in one of the most widespread digitally mediated genres of science popularisation, the TED talks. We adopt a multimodal discourse analysis approach to explore how the presenter orchestrates her speech, visuals on slides, and hand gestures to achieve the communicative purposes of the TED talk. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Typical traits include the use of humour as an endemic characteristic (Scotto di Carlo, 2013), an informal register that encourages participation and proximity (Scotto di Carlo, 2014), reduced technicality and the presence of personal anecdotes (Mattiello, 2017), the use of markers of engagement, together with epistemic verbs for the expression of stance (Caliendo & Compagnone, 2014;Compagnone, 2014). From a multimodal perspective, research has shown that different semiotic resources (including gestures and visuals as slides with images and videos, see Harrison, 2021;Jiang & Lim, 2022;Wu & Qu, 2020;Xia, 2023) can be significantly co-deployed with words in this genre of popularisation, thus contributing to multimodal ensembles (Kress, 2010), i.e., combinations of meaningmaking resources or modes, of different degrees of complexity and with a varied distribution across distinct knowledge domains (Masi, 2019(Masi, , 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…Typical traits include the use of humour as an endemic characteristic (Scotto di Carlo, 2013), an informal register that encourages participation and proximity (Scotto di Carlo, 2014), reduced technicality and the presence of personal anecdotes (Mattiello, 2017), the use of markers of engagement, together with epistemic verbs for the expression of stance (Caliendo & Compagnone, 2014;Compagnone, 2014). From a multimodal perspective, research has shown that different semiotic resources (including gestures and visuals as slides with images and videos, see Harrison, 2021;Jiang & Lim, 2022;Wu & Qu, 2020;Xia, 2023) can be significantly co-deployed with words in this genre of popularisation, thus contributing to multimodal ensembles (Kress, 2010), i.e., combinations of meaningmaking resources or modes, of different degrees of complexity and with a varied distribution across distinct knowledge domains (Masi, 2019(Masi, , 2020a.…”
Section: Introductionmentioning
confidence: 99%